Determinants of User Satisfaction with Fixed Broadband Internet Services during the Covid-19 Pandemic - Thu, Trinh Thi; Hue, Truong Thi (International Journal of Business, Management and Economics, 2022)
The internet has made the world a smaller place and has several functions in providing exposure to other individuals, locations, ideas, global access and opportunities all over the world. Arguably all these functions require users to be satisfied with internet services to achieve their objectives. This paper reports findings from 171 users with fixed broadband services during Covid-19 pandemic in Danang, Vietnam. It argues that in certain disruptive and unfavorable events, satisfaction involves the conative, which is to continue the commitment with the current provider, and not likely to switch to new services or other brands. The study identifies that the customer services, value- added services, price structure, network quality, the convenience and responsiveness are important determinants and significantly adjuncts to the generation of satisfaction.